Role of zinc-coated urea fertilizers in improving nitrogen use efficiency, soil nutritional status, and nutrient use efficiency of test crops - Abdullah, Bilal; Niazi, Muhammad Bilal Khan; Jahan, Zaib; Khan, Obaid; Shahid, Ameen; Shah, Ghulam Abbas; Azeem, Babar; Iqbal, Zahid; Mahmood, Abid (Frontiers in Environmental Science, 2022)
The rise in global population, urbanization, and desertification pushes the farming community toward intensive cropping to meet the augmented food demands with consequent exhaustion of soil’s nutritional status and fertility. In recent times, environmental pollution and cost of crop production have been enhanced due to excessive and inefficient use of nitrogenous fertilizers. As an abatement strategy, seven different coated urea fertilizers, namely, gelatin-coated (G), zinc oxide with gelatin-coated (ZnOG), zinc oxide-coated (ZnO), sonicated zinc oxide-coated (ZnO-Son), zinc oxide with molasses-coated (ZnOM), zinc sulfate with molasses-coated (ZnSM), and zinc sulfate-coated (ZnS) were prepared in a fluidized bed coater. The coated samples were characterized through XRD, SEM, and FTIR techniques, while a crushing strength test was carried out to assess the impact of inventory operations on physical integrity of coated prills. Pot tests with ryegrass (Lolium perenne) as a test crop were carried out to evaluate the effect of coated urea fertilizers on yield and nitrogen (N) and zinc uptake in order to enhance nitrogen use efficiency and reduce pollution. Our results suggest that the affinity between urea surface and coating materials was of physical nature. All zinc oxide- or gelatin-coated treatments significantly increased the dry matter yield, nitrogen uptake, apparent nitrogen recovery (ANR), zinc uptake, and apparent zinc recovery (AZnR). ZnOG was proved to be the best sample in terms of balancing soil chemical properties with improved soil nutrition and producing best with plant yield (94% higher than UC), N uptake (75% higher than UC), Zn uptake (450% higher than UC), and nitrogen use efficiency (48 vs. 23% for UC). Our results suggest that the use of such coated fertilizers can lead to improve yields, nutritional values of crops, and overall agro-ecological scenario.